A model for assessment leadership: A systematic document analysis in the development of an assessment leadership experience questionnaire - Escote, Alixander Haban (Animo Repository, 2023)
The study developed an Assessment Leadership Experience (ALEx) Questionnaire that measured the perceived ALEx levels and the perceived levels of importance of assessment leadership competencies of school principals. The results of the study were used in developing a model for assessment leadership for school principals vis-à-vis their perceived ALEx levels and the perceived levels of importance of assessment leadership competencies to their job as school principals. The study employed a mixed methods research design using quantitative research method as the primary approach, i.e., an online survey questionnaire where data were gathered from the comprehensive sample of respondents, and qualitative method as the supporting approach, i.e., document analysis of published research and literature about assessment, assessment literacy, assessment practices, and assessment leadership. After seven simple and manual coding cycles, 10 assessment leadership categories, 30 assessment leadership concepts, and 80 assessment leadership themes emerged. Responses in the online survey were analyzed using the Statistical Package for Social Science, using frequency distribution and percentages and weighted mean and standard deviation. To qualify the degree of the responses of the respondents, limits of parameters were used for the perceived ALEx levels of school principals, which are awareness level, emerging level, practicing level, leading level, and transforming level, and for the perceived levels of importance of assessment leadership competencies of school principals, which are least essential, less essential, essential, more essential, and most essential. Results of the online survey show that the perceived ALEx levels of school principals are at the leading level. In contrast, the perceived levels of importance of assessment leadership competencies of school principals are more essential. All ten assessment leadership categories are more essential, and seven are above the composite mean. The seven categories that are above the composite mean include the following: (1) assessment leadership knowledge and attitude; (2) classroom assessment and classroom assessment data; (3) formative assessments; (4) test construction and measurement and evaluation; (5) focusing on literacy and leading a culture of change; (6) student learning, student learning targets, and student learning outcomes; and (7) assessment tools and processes, policies and practices, and alternatives. A model for assessment leadership for school principals with ten domains, 18 strands, and 44 competencies was developed by coding the assessment leadership themes, concepts, and categories. Keywords: assessment practices, assessment literacy, assessment leadership, assessment leadership competencies, perceived assessment leadership experience levels